Li/air Flow Battery Employing Ionic Liquid Electrolytes. Issue 1 (2nd November 2015) - Grande, Lorenzo; Ochel, Anders; Monaco, Simone; Mastragostino, Marina; Tonti, Dino; Palomino, Pablo; Paillard, Elie; Passerini, Stefano
Abstract: Despite the considerable initial optimism behind its development and prospective commercialization, the Li/air battery chemistry has now reached a mature stage of development, which has served to highlight the main underlying technological limitations, as well as what can realistically be expected from it. One of the main challenges is the control of the discharge product morphology, that is, Li2 O2, onto the positive electrode. In this article, we show how the three‐phase configuration required to ensure cell operation can be induced in a two‐phase system made of mesoporous carbon and an ionic liquid electrolyte [ N ‐butyl‐ N ‐methylpyrrolidinium bis(trifluoromethane sulfonyl)imide, Pyr14 TFSI] by means of an oxygen‐bubbling device (OBD) and a peristaltic pump. The use of a non‐flammable, non‐volatile electrolyte ensures long‐term, extensive discharging (up to 4.78 mAh cm −2 ), as well as operation at temperatures higher than room temperature. Abstract : Going with the flow: The need for better batteries has fueled research in high‐risk/high‐reward cell chemistries such as lithium/air. In this work, we propose a novel two‐phase Li/air flow battery that operates under semi‐ambient conditions thanks to the use of an ionic‐liquid‐based electrolyte. The high areal capacity attained (4.78 mAh cm −2 ) and the self‐contained configuration make it appealing for automotive applications.